2016
DOI: 10.1016/j.str.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Molecular Dimension of a RAGE-Ligand Complex Triggers RAGE Signaling

Abstract: Summary The weak oligomerization exhibited by many transmembrane receptors has a profound effect on signal transduction. The phenomenon is difficult to structurally characterize due to the large sizes of and transient interactions between monomers. The receptor for advanced glycation end products (RAGE), a signaling molecule central to the induction and perpetuation of inflammatory responses, is a weak constitutive oligomer. The RAGE domain interaction surfaces that mediate homo-dimerization were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 72 publications
(136 reference statements)
1
65
0
1
Order By: Relevance
“…These ligands bind to the extracellular domains of RAGE in a heterogeneous manner; although the extracellular V-type immunoglobulin (Ig) domain binds to many of the ligand families, the binding sites on the V-domain are multiple and spatially distinct. Further, ligands may also bind at the extracellular C1 and C2-type Ig domains, thereby further diversifying the complexity of the RAGE-ligand interactions (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…These ligands bind to the extracellular domains of RAGE in a heterogeneous manner; although the extracellular V-type immunoglobulin (Ig) domain binds to many of the ligand families, the binding sites on the V-domain are multiple and spatially distinct. Further, ligands may also bind at the extracellular C1 and C2-type Ig domains, thereby further diversifying the complexity of the RAGE-ligand interactions (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments by Shekhtman and colleagues illustrated that RAGE forms constitutive homo-dimers through its extracellular VC1 and C2 domains and that upon ligand engagement, the molecular dimension of RAGE increases, thereby allowing its cytoplasmic domain to recruit DIAPH1 and to initiate signaling 50 . In that work, mutations of DIAPH1 were prepared, which indicated that full-length DIAPH1 is required for RAGE signal transduction stimulated by RAGE ligands such as S100B.…”
Section: Rage and Signal Transductionmentioning
confidence: 99%
“…In addition to the study of the biological implications of RAGE and DIAPH1 in diabetes-and vascular disease-associated disease models, extensive efforts have unveiled the nature of the interaction of the cytoplasmic domain of RAGE with the FH1 (formin homology domain 1) of DIAPH1. Shekhtman's laboratory has shown that the amino acid residues R5 and Q6 in the RAGE cytoplasmic domain are required for the interaction with DIAPH1 and that the induction of the association of RAGE homo-dimers on the cell surface by RAGE ligands increases the molecular dimension of RAGE, thereby recruiting DIAPH1 and, consequently, triggering the activation of signal transduction pathways [22,23].…”
Section: Rage-diaph1novel Therapeutic Target For Diseases Of Ragementioning
confidence: 99%